Micropropagation of banana cv. Williams through temporary immersion system: Response to explant density and plant growth regulators (Agroindustrial Science, 2025)
Banana presents issues with conventional propagation due to a low multiplication rate and diseases. Micropropagation allows the mass production of seedlings with better agronomic characteristics under controlled laboratory conditions, it uses explants and plant growth regulators (PGR) at different stages. Plant tissue culture (PTC) allows nutrients to be provided through the use of bioreactors with a temporary immersion system (TIS), the immersion of the plant material in the culture medium periodically prompts better individuals by facilitating the interaction of the plant material with the culture medium. The aim of this study was to evaluate the response to micropropagation of banana cv. Williams during the multiplication stage using RITA® (Recipient for Automated Temporary Immersion) bioreactors. For this purpose, two experiments were carried out: one using different explant density and the other one using different concentrations of plant growth regulators. The explants of banana correspond to the fourth subculture obtained from shoot meristems. The results obtained after 21 days of culture showed high multiplication rates and highlighted the usefulness of bioreactors with temporary immersion systems (TIS) to successfully propagate banana.
Keywords: banana; plant biotechnology; bioengineering; explant density; plant growth regulators